An Overview of Japanese Encephalitis - Rajeshwar Reddy Kasarla; Rekha Sudi; Laxmi Pathak (Journal of Universal College of Medical Sciences, 2024)
INTRODUCTION Japanese encephalitis virus (JEV) is a ﬂavivirus, is the main cause viral encephalitis, endemic in South-East Asia, and Western Paciﬁc regions and has become a major public health problem worldwide. JEV is transmitted to humans through the bite of an infected mosquito, mainly Culex tritaeniorhynchus that breeds in ﬂooded rice ﬁelds, marshes, standing water around planted ﬁelds. Reservoir hosts are Adreid birds (herons and egrets), and pigs serve as ampliﬁer hosts. Though infections are usually asymptomatic, the symptomatic Japanese encephalitis has a case fatality rate as high as 30%. Permanent neurologic or psychiatric sequelae can occur in 30-50% of those with encephalitis. There is no antiviral drug available. Treatment is mainly supportive and symptomatic. Safe and effective vaccines are available to prevent Japanese encephalitis. This article reviews recent advancements in diagnostic methods, prophylactics as well as therapeutic options and challenges to combat this zoonotic emerging and remerging viral encephalitis.